The Effect of Retention Rate, Debt to Equity Ratio, and Current Ratio on Company Sustainable Growth Rate - Halim, Kusuma Indawati (InFestasi, 2024)
This study examines the impact of financial metrics on sustainable growth, defined as the maximum rate at which a company can grow without changing its financial leverage, a concept supported in recent studies on corporate growth strategies. The analysis focuses on the retention ratio, debt-to-equity ratio, and current ratio. Data is sourced from non-financial companies listed on the Kompas 100 Index on the Indonesia Stock Exchange, selected based on consistent financial reporting and comprehensive data availability during this period. Utilizing a panel data regression model with Stata 17 software, the findings reveal that the retention ratio positively affects sustainable growth, supporting the idea that reinvesting profits promotes long-term company growth. Conversely, DER has a negative impact, indicating that higher leverage increases financial risk. The current ratio does not significantly affect sustainable growth within this model. These results emphasize the importance of strategic financial management, particularly in optimizing retention and leverage, to foster sustainable growth. The study offers stakeholders and legislators practical advice on how to encourage financial practices that foster long-term organizational growth.